1998
DOI: 10.1038/bjc.1998.104
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between serum matrix metalloproteinase-2 and its inhibitor as a predictor of recurrence of urothelial cancer

Abstract: Summary Serum levels of matrix metalloproteinase-2 (MMP-2) and tissue inhibitor of metalloproteinases-2 (TIMP-2) were evaluated as prognostic indicators of the recurrence of urothelial cancer. Sera were obtained from 127 healthy control subjects and 97 urothelial cancer patients who underwent complete resection and were measured for MMP-2 and TIMP-2 using a one-step enzyme immunoassay. The relationship between the serum MMP-2/TIMP-2 ratio and the recurrence of urothelial cancer was examined. The mean serum MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 17 publications
(20 reference statements)
1
32
0
5
Order By: Relevance
“…High expression levels of MMP-2, MMP-9, MT1-MMP and TIMP-2 in peritumoral stromal cells of ovarian carcinoma patients correlate with poor survival. 43 Increased expression levels of MMP-2 have been associated with unfavorable outcome also in gastric cancer, 44 in urothelial cancer 45 and in early stage non-small cell lung cancer. 46 Overexpression of MMP-9 is related to well differentiated hepatocellular carcinoma 47 and to recurrence in early non-small cell lung carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…High expression levels of MMP-2, MMP-9, MT1-MMP and TIMP-2 in peritumoral stromal cells of ovarian carcinoma patients correlate with poor survival. 43 Increased expression levels of MMP-2 have been associated with unfavorable outcome also in gastric cancer, 44 in urothelial cancer 45 and in early stage non-small cell lung cancer. 46 Overexpression of MMP-9 is related to well differentiated hepatocellular carcinoma 47 and to recurrence in early non-small cell lung carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…53 In urothelial cancer, a high serum MMP-2/TIMP-2 ratio predicts poor prognosis 104 or recurrence. 105 On the other hand, Vuoristo et al 106 found no prognostic value for serum total MMP-2 levels in patients with advanced cutaneous melanoma. Increased expression of MMP-3 in tumour cells of SCLC (107) and in serum of urothelial carcinoma patients 53 have shown only limited prognostic value.…”
Section: Mmps As Prognostic Survival Markers In Cancermentioning
confidence: 98%
“…Gohji et al no hallaron ninguna diferencia en niveles circulantes de MMP-2 entre neoplasia superficial y controles 4 . Más tarde este grupo refirió un riesgo más alto de recurrencia y progresión cuando la relación MMP-2/TIMP-2 era elevada 8 . No hay duda de que existe un proceso regulatorio entre metaloproteinasas e inhibidores de tejido en la progresión tumoral y desarrollo de metástasis.…”
Section: Discussionunclassified
“…(6) 10 Orina/sobrenadante Zimografía MMP-9 y MMP-2 detectada en pacientes con cáncer Bianco et al (7) 65 Lavado vesical Zimografía MMP-9 correlaciona con estadio y grado Gohji et al (8) 224 Suero ELISA Alta relación MMP-2/TIMP-2 baja supervivencia Kanayama et al (9) 41 Tejido/congelado RT-PCR MMP-2 & TIMP-2 correlacionado con estadio Hamasaki et al (10) Línea celular T24 RT-PCR, EIA Desequilibrio MMP-2/TIMP-2 implica progresión Furukawa et al (11) Líneas UCT1 y 2 RT-PCR MMP-2 más alto en implantes línea UCT-1 invasivos Ozdemir et al (12) 33 Orina/sobrenadante ELISA MMP-9 detectable en cáncer pero no en controles Ozdemir et al (12) 60 Tejido/parafina Inmunohistoquímica MMP-9 correlacionada con lisis de membrana basal Kanda et al (13) 61 Tejido/congelado Zimografía MMP-2 correlaciona con grado, estadio y resultado Monier et al (14) 101 Orina ELISA, inmunotransferencia…”
Section: Muestras Y Aislamiento Del Arnunclassified